2017
DOI: 10.23986/afsci.64417
|View full text |Cite
|
Sign up to set email alerts
|

The effects of legume seeds on the lactation performance of dairy cows fed grass silage-based diets

Abstract: The aim was to study if locally produced organic legume seeds as protein supplement could improve the performance of dairy cows. The experiment was a cyclic change over design were the control diet consisted of grass silage and barley (60:40) on a dry matter (DM) basis. Barley was replaced with rapeseed expeller (RSE), or isonitrogenous supplements of peas, untreated field beans (UFB), heat-treated FB (TFB) or a lower level of TFB (TFB-low) that provided the same dietary metabolizable protein concentrations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
5
17
0
Order By: Relevance
“…In contrast, the NDF concentration of FB was only half that of RSM, and only 2% of the NDF in FB was indigestible, whereas this value was 53% in RSM. These values are in good agreement with Ramin et al (2017). Similarly, the AA concentration with very low levels of methionine and moderate levels of histidine is typical for FB (Aguilera et al, 1992;Duc et al, 1999).…”
Section: Composition Of Protein Feedssupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, the NDF concentration of FB was only half that of RSM, and only 2% of the NDF in FB was indigestible, whereas this value was 53% in RSM. These values are in good agreement with Ramin et al (2017). Similarly, the AA concentration with very low levels of methionine and moderate levels of histidine is typical for FB (Aguilera et al, 1992;Duc et al, 1999).…”
Section: Composition Of Protein Feedssupporting
confidence: 79%
“…However, the protein value of FB may be impaired by their considerably high rumen degradability and low concentration of methionine (Aguilera et al, 1992;Duc et al, 1999;Luke, 2019), which is often the limiting AA for milk production (e.g., Pisulewski et al, 1996). Indeed, compared with rapeseed, FB have resulted in lower milk and protein yields in dairy cows (Puhakka et al, 2016;Ramin et al, 2017;Halmemies-Beauchet-Filleau et al, 2018). Previously, balancing the AA supply in metabolizable protein has increased milk and protein yields and improved the conversion of feed N into milk protein (N use efficiency, NUE; Haque et al, 2012), consequently leading to decreased N emissions to the environment.…”
mentioning
confidence: 99%
“…Dairy cow feeding trial. In the current study, extrusion of faba beans affected neither dry matter intake (results not shown) nor milk yield (Table 6), these findings are in agreement with the results reported by Ramin et al (2017). No effect on lactation performance in the study could be also related to relatively small amount of faba beans in the diet compared to other studies.…”
Section: Resultssupporting
confidence: 92%
“…As the feed efficiency is mainly driven by dry matter intake (DMI), no difference between the groups was expected. These results corroborate the findings of Ramin et al (2017) who reported no effect on feed efficiency (kg ECM kg -1 DMI) when feeding untreated or heat-treated field beans to dairy cows. In addition, similar findings by Cherif et al (2018) indicate feed efficiencies of 1.40 and 1.39 of cows fed either ground or rolled faba beans.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation